Comparison of Three Methods to Assess Therapeutic Quality Control of Treatment with Vitamin K Antagonists - Hutten, Barbara A.; Prins, Martin H.; Ken Redekop, W.; Tijssen, Jan G.P.; Heisterkamp, Siem H.; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
During treatment with vitamin K antagonists, International Normalized Ratios (INR) are determined periodically to maintain a therapeutic level of anticoagulation. We evaluated two existing methods for therapeutic quality control (linear interpolation and equidivision), with regard to their validity and reproducibility. In addition, we proposed and evaluated a (hybrid) method that takes into account potential effects of dosage modifications when INRs are far out of the target range. Validity was assessed by deleting intermediary INR results and estimating this INR based on the two surrounding INRs with each of the three methods. The estimated INRs were then compared with the observed INR.Reproducibility of time spent in an INR range was evaluated for each of the three methods by deleting at random increasing proportions of INRs and comparing these estimates with the situation without deletions. We found that estimates of time spent in INR categories obtained with equidivision were most reproducible, but least valid. The hybrid method showed slightly higher validity and reproducibility in comparison with linear interpolation. Since these differences were small, linear interpolation is preferable to the hybrid method, since the calculations involved are easier.
Keywords: Factor IX; translational initiation; CHO cells; factor IX production; factor IX intron I